“Foreign migrant women's perceptions of obstetric care in the Cape Town metro pole.” - Hendricks, Fahad (Department of Obstetrics and Gynaecology, 2025)
This study explores the maternal healthcare experiences of nine foreign migrant women who received obstetric care in the Cape Town metropole. The Republic of South Africa's legislation enshrines the right to health for all who live within the country's borders, regardless of residency status. In practice however, foreign migrants can experience significant challenges and, in the Cape Town metropole how these women experience obstetric care has not been a focus of scholarly interrogation. With this study I hope to establish the factors that influence migrant women's experiences positively or negatively and to utilise the knowledge gained from their experiences to enhance pregnancy care of migrant women in the longer term. A literature review was performed covering the areas of migration to South Africa, migrant women's health, migrant's health challenges and official South African health care policies. Data was collected by doing one on one, open-ended and semi-structured interviews with nine foreign migrant women from seven different countries and with two key stakeholders employed at two of Cape Town's largest refugee centres. The interviews were recorded, professionally transcribed and then data inductively coded using thematic analysis. Thematic analysis was used since it is a way to extract descriptive information concerning the experiences of migrant women in Cape Town and to construct meaning, in order to understand their perceptions about the obstetric care. The findings indicate that the attitudes & behaviours of staff, language, prior traumatic experiences, degree of assimilation and healthcare systemic issues are some of the chief factors that influence perception of care. Xenophobia and dismissive behaviour were the main issue with staff but that was juxtaposed against some excellent and compassionate care received. Some of the women struggled to communicate the nature of their problems and being understood but also found understanding local staff a significant barrier. Having had to endure staff attitudes and behaviours can reasonably be agreed to have delayed monitoring or intervention. Language barriers resulted in adherence issues with medications, potential missed appointments, issues around informed consent and missed opportunities at health promotion. The women had a poor understanding of the local healthcare system's design and had expecta tions in relation to their own experience of the system in origin countries. When these expectations were not met, it was perceived as poor. A key challenge was the failure of the facilities to recognise the asylum documentation and the rights afforded to those who had them. The reasons for fleeing their countries included warfare, geno cide, political turmoil and economic deprivation. The journeys to Cape Town were fraught with further trauma and this made the women vulnerable to mental health is sues which also impacted their perceptions of care. Further, a traumatic birth in Cape Town carried significant sway over how further births in Cape Town were viewed. It is clear from this study that multiple, complex factors influence the way foreign mi grant women perceive their care. These factors are personal and unique to each indi vidual but there were commonalities. Trained interpreters, cultural sensitivity training, education surrounding documentation, allowing birth partners to be present during visits and births, extra safety checks on perinatal mental health for first time births in Cape Town and a more robust, confidential and accountable complaints system were recommendations by this cohort.